2006
DOI: 10.1377/hlthaff.25.w74
|View full text |Cite
|
Sign up to set email alerts
|

Medical Bankruptcy: Myth Versus Fact

Abstract: David Himmelstein and colleagues recently contended that medical problems contribute to 54.5 percent of personal bankruptcies and threaten the solvency of solidly middle-class Americans. They propose comprehensive national health insurance as a solution. A reexamination of their data suggests that medical bills are a contributing factor in just 17 percent of personal bankruptcies and that those affected tend to have incomes closer to poverty level than to middle class. Moreover, for national health insurance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 6 publications
6
47
0
1
Order By: Relevance
“…By comparison, we know of very little work that, like us, uses rich administrative data and the sharp timing of health events to study the economic consequences of adverse health events in the United States. 2 Finally, our findings contribute directly to the controversial, high-profile literature on "medical bankruptcies", which has concluded that medical events can explain between 17 and 62 percent of all consumer bankruptcies (Himmelstein et al 2005(Himmelstein et al , 2009; Dranove and Millenson 2006). Consistent with this "medical bankruptcy" literature, we estimate that hospital admissions are associated with statistically significant increased rates of consumer bankruptcy for non-elderly adults (but not for the elderly).…”
Section: Introductionsupporting
confidence: 80%
“…By comparison, we know of very little work that, like us, uses rich administrative data and the sharp timing of health events to study the economic consequences of adverse health events in the United States. 2 Finally, our findings contribute directly to the controversial, high-profile literature on "medical bankruptcies", which has concluded that medical events can explain between 17 and 62 percent of all consumer bankruptcies (Himmelstein et al 2005(Himmelstein et al , 2009; Dranove and Millenson 2006). Consistent with this "medical bankruptcy" literature, we estimate that hospital admissions are associated with statistically significant increased rates of consumer bankruptcy for non-elderly adults (but not for the elderly).…”
Section: Introductionsupporting
confidence: 80%
“…Qualitative studies indicate that households falling into poverty traps report health expenditures to be one of the critical reasons for poverty (Sauerborn, Adams, & Hien, 1996;Narayan et al, 2000;Krishna et al 2003). Much of the quantitative literature on medical impoverishment comprising observational studies and cross-sectional correlations between household expenditures, poverty levels, and health expenditures is unable to provide causal evidence (Gottlieb, 2000;Liu, Rao, & Hsiao, 2003;Xu et al, 2003;Himmelstein et al 2005;van Doorslaer et al 2005;Dranove & Millenson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous analysis has documented the correlation between insurance status and financial outcomes (e.g., Gross and Souleles 2002), or shown that individuals with high medical expenses are overrepresented among bankruptcy filers (e.g., Dranove andMillenson 2006, Himmelstein et al 2005). However, these studies are unable to address the common empirical problem that financial outcomes and health insurance status or medical bills may be correlated because of unobserved factors, such as risk preference, or that financial shocks may themselves cause poor health.…”
mentioning
confidence: 99%